The doctoral research abstracts. Vol:12 2017 / Institute of Graduate Studies, UiTM - Universiti Teknologi MARA, Institute of Graduate Studies (Institute of Graduate Studies, 2017)
Foreword: Congratulation to IGS on your continuous efforts to publish the 12th issue of the Doctoral Research Abstracts which highlights research in various disciplines from science and technology, business and administration to social sciences and humanities. This research abstract features the abstracts from 71 PhD doctorates who will receive their scrolls in this 87th UiTM momentous convocation ceremony. To the 71 doctorates, you have most certainly done UiTM proud by journeying through the scholarly world with its endless challenges and obstacles, and by persevering right till the very end. Graduands, your success in achieving the highest academic qualification has demonstrated that you have indeed engineered your destiny well. The action of registering for a PhD program was not by chance but by choice. It was a choice made to realise your self-actualization level that is the highest level in Maslow’s Hierarchy of Needs, while at the same time unleashing your potential in scholarly research. Again, congratulations to all PhD graduates. As you leave the university as alumni we hope a new relationship will be fostered between you and the faculty in soaring UiTM to greater heights. I wish you all the best in your future endeavor. Keep UiTM close to your heart and be our ambassador wherever you go. / Prof Emeritus Dato’ Dr Hassan Said Vice Chancellor Universiti Teknologi MARA